PERAN EKONOMI DAN KEUANGAN SYARIAH PADA MASA PANDEMI COVID-19 - Gia Dara Hafizah (LIKUID: Jurnal Ekonomi Industri Halal, 2021)
The spread of the COVID-19 epidemic that originated in Wuhan has made humans all over the world have to do many things to be able to avoid a virus that has not yet been found a cure. There are many things that can be done to stop the spread of COVID-19, from diligently washing hands, maintaining body immunity by eating nutritious foods and exercising, and maintaining a minimum distance of 1 (one) meter between individuals. For the last point, then a policy called social distancing is applied, where everything is expected to be done from home, be it teaching and learning activities or economic activities. Unfortunately, every thing has its advantages and disadvantages. In the economic field, the implementation of social distancing then becomes an obstacle to economic growth itself. Then, in the midst of an ongoing pandemic, will Islamic Economics still be able to help deal with the economic shocks that occurKey words : islamic economy, zakat, financing, capital, covid-19